The effect of credence attributes on willingness to pay a premium for organic food: A moderated mediation model of attitudes and uncertainty - Huo, Hong; Jiang, Xinyu; Han, Chunjia; Wei, Sheng; Yu, Dingyao; Tong, Yang (Frontiers in Psychology, 2023)
With consumers' concerns about food safety and the environment growing, the interest in organic food has increased. However, due to the late start of the organic food market in China, the market size of the Chinese organic food industry is still relatively small. This study aims to examine whether organic food credence attributes have an impact on consumers' attitudes and willingness to pay a premium (WTPP), in order to provide valuable information to facilitate the development of the organic food market in China. The study surveyed 647 respondents in China. Structural equation modelling (SEM) was utilized to verify the model and test the relationships among the constructs. The results indicate that credence attributes stimulates consumers’ attitudes and increases consumers' WTPP. Utilitarian attitudes and hedonistic attitudes play a partially mediating role in the relationship between credence attributes and WTPP. Uncertainty negatively moderates the role between utilitarian attitudes and WTPP, while it positively moderates the role between hedonistic attitudes and WTPP. The findings can provide an important theoretical basis for companies to deeply understand the motivation of consumer groups and develop organic food marketing strategies.